Analisis Kemampuan Membaca Permulaan Siswa Kelas II SD Berdasarkan Asesmen EGRA di SD Negeri Kaliduren Sleman - Vika Farida; Muhardila (Science and Education Journal (SICEDU), 2026)
This study aims to examine the early reading skills of second-grade students based on the indicators found in the EGRA instrument. The researcher used a qualitative approach with a descriptive research design to provide an in-depth description of the students’ reading skills. The researcher selected second-grade elementary school students as the research subjects at SD Negeri Kaliduren. The study collected data through reading tests using the EGRA instrument, observations of students’ individual reading activities, interviews with classroom teachers, students, and parents, as well as documentation. The researcher analyzed the data through the stages of data reduction, data presentation, and systematic conclusion drawing. The researcher employed methodological triangulation and source triangulation to ensure the validity of the research data. The results indicate that students’ early reading skills vary across the observed indicators. Most students can identify letter names and letter sounds, as well as read syllables and words commonly used in daily life. However, some students still experienced difficulties when reading randomly presented words, especially those with more complex phonological structures.These difficulties were manifested through letter pronunciation errors, omission of letter sounds, stuttering, and a lack of reading fluency. This study concludes that students’ early reading skills are influenced by learning motivation, reading concentration, and the support of the learning environment at school and at home.